PENGGUNAAN MEDIA BIG BOOK DALAM MENINGKATKAN KEMAMPUAN MEMBACA SISWA SEKOLAH DASAR - Three Rahmadona; Firman; Desyandri (STKIP Subang, 2022)
Low interest and ability to read is a serious problem in the field of education continue to work on how to overcome it. One of the media that can be used to improve students' reading skills is Big Book media which can be created according to the teacher's creativity. This research aims to provide information to teachers, principals, and parents regarding the use of Big Book media to improve elementary school students' reading skills. The method used in this research is literature study or library research. The researcher traces the data, then reads and records the results needed to obtain the information. The data collected was analyzed using the content analysis method. The results of the analysis of 15 articles concluded that the use of Big Book media improved students' reading skills. This is based on an increase in reading scores from before using Big Book media to after using Big Book media in learning and the SPSS test was carried out to see the effect.